Prolonged sound exposure has different effects on increasing neuronal size in the auditory cortex and brainstem - Lu, H P; Syka, J; Chiu, T W; Poon, Paul W F (Hearing research, 2014)
Tone at moderate levels presented to young rats at a stage (postnatal week-4) presumably that has passed the cortical critical period still can enlarge neurons in the auditory cortex. It remains unclear whether this delayed plastic change occurs only in the cortex, or reflects a change taking place in the auditory brainstem. Here we compared sound-exposure effects on neuronal size in the auditory cortex and the midbrain. Starting from postnatal day 22, young rats were exposed to a low-frequency tone (4 kHz at 65 dB SPL) for a period of 3 (postnatal day 22-25) or 7 (postnatal day 22-29) days before sacrifice. Neurons were analyzed morphometrically from 7 μm-thick histological sections. A marked increase in neuronal size (32%) was found at the cortex in the high-frequency region distant from the exposing tone. The increase in the midbrain was even larger (67%) and was found in both the low and high frequency regions. While cell enlargements were clear at day 29, only in the high frequency region of the cortex a slight enlargement was found at day 22, suggesting that the cortical and subcortical changes are synchronized, if not slightly preceded by the cortex. In contrast, no changes in neuronal size were found in the cochlear nucleus or the visual midbrain. Such differential effects of sound-exposure at the auditory centers across cortical and subcortical levels cannot be explained by a simple activity-driven change occurring earlier in the brainstem, and might involve function of other structures as for example the descending auditory system.
Keywords: neuroplasticita; Sound; sluch; nucleus cochlearis; neurony; Acoustic Stimulation; Brain Stem; Time Factors; Animals; Bone and Bones; mezencefalon; časové faktory; Cochlear Nucleus; Neurons; kosti a kostní tkáň; krysa rodu Rattus; Auditory Pathways; sluchové korové centrum; Rats; Rats, Sprague-Dawley; Neuronal Plasticity; sluchová dráha; Hearing; zvířata; potkani Sprague-Dawley; akustická stimulace; zvuk; Auditory Cortex; Mesencephalon; mozkový kmen